Global Cooperation in Combating Sea Piracy: The Factors behind Global Piracy Trends - Radillah Khaerany; Maskun Maskun (Faculty of Law, Hasanuddin University, 2016)
The rising number of sea travel is followed by the emerging number of sea crimes such as sea piracy and maritime terrorism. In recent two decades, the number of crimes on the sea have shown an alarming figure, where areas with a dense traffic of vessels such as the Gulf of Aden and Malacca Strait becomes the hot spots for piracy crime. The main reason behind the emerging of modern piracy is the increasing number of sea transported goods which create a significant opportunity to be a huge target of crime considering the drives behind piracy is financial reason. Some area of sea piracy took place commonly in Africa and Southeast Asia.